Topography shapes the structure, composition and function of tropical forest landscapes - Tommaso Jucker; Boris Bongalov; David F. R. P. Burslem; Reuben Nilus; Michele Dalponte; Simon L. Lewis; Oliver L. Phillips; Lan Qie; David A. Coomes (Ecology Letters, 2018)
Topography is a key driver of tropical forest structure and composition, as it constrains local nutrient and hydraulic conditions within which trees grow. Yet, we do not fully understand how changes in forest physiognomy driven by topography impact other emergent properties of forests, such as their aboveground carbon density ( ACD ). Working in Borneo – at a site where 70‐m‐tall forests in alluvial valleys rapidly transition to stunted heath forests on nutrient‐depleted dip slopes – we combined field data with airborne laser scanning and hyperspectral imaging to characterise how topography shapes the vertical structure, wood density, diversity and ACD of nearly 15 km 2 of old‐growth forest. We found that subtle differences in elevation – which control soil chemistry and hydrology – profoundly influenced the structure, composition and diversity of the canopy. Capturing these processes was critical to explaining landscape‐scale heterogeneity in ACD , highlighting how emerging remote sensing technologies can provide new insights into long‐standing ecological questions.